A Multi-action PtIV Conjugate with Oleate and Cinnamate Ligands Targets Human Epithelial Growth Factor Receptor HER2 in Aggressive Breast Cancer Cells - Kostrhunova, Hana; Zajac, Juraj; Markova, Lenka; Brabec, Viktor; Kasparkova, Jana (Angewandte Chemie (International ed. in English), 2020)
HER2-positive breast cancer is an aggressive subtype that typically responds poorly to standard chemotherapy. To design an anticancer drug selective for HER2-expressing breast cancer, a PtIV prodrug with axial oleate and cinnamate ligands was synthesized. We demonstrate its superior antiproliferative activity in monolayer and 3D spheroid models; the antiproliferative efficiency increases gradually with increasing expression of HER2. The results also suggest that the released PtII compound inhibits the proliferation of cancer cells by a DNA-damage-mediated mechanism. Simultaneously, the released oleic and cinnamic acid can effectively inhibit HER2 expression. To our knowledge, this is the first platinum-based complex inhibiting HER2 expression that does not contain protein or peptide. Moreover, this PtIV prodrug is capable of overcoming the resistance of cancer stem cells (CSCs), inducing death in both CSCs and differentiated cancer cells. Thus, the results substantiate our design strategy and demonstrate the potential of this approach for the development of new, therapeutically relevant compounds.
Keywords: cinnamáty; Coordination Complexes; nádory prsu; Cell Proliferation; Humans; Cell Differentiation; Molecular Structure; Antineoplastic Agents; nádorové buněčné linie; breast cancer; metals in medicine; Breast Neoplasms; protinádorové látky; Platinum; Drug Screening Assays, Antitumor; Receptor, ErbB-2; screeningové testy protinádorových léčiv; MFC-7 buňky; proliferace buněk; Cinnamates; receptor erbB-2; platinum; Cell Survival; kyselina olejová; viabilita buněk; MCF-7 Cells; prodrugs; platina; lidé; komplexní sloučeniny; medicinal chemistry; Cell Line, Tumor; buněčná diferenciace; molekulární struktura; Oleic Acid